PENGARUH DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KESYAHBANADARAN DAN OTORITAS PELABUHAN KELAS I AMBON - Septiani Siahaya; Pocerattu V. Alfonso; Zany I Aunalal (Jurnal Administrasi Terapan, 2023)
The Ambon Class I Harbormaster and Port Authority Office is a Technical Implementation Unit (UPT) which has the task of carrying out supervision in the field of shipping safety and security, coordinating government activities at ports as well as regulation, control and commercial supervision. One that affects performance is creating good work discipline. However, there are still some problems in employee discipline. So this study aims to influence discipline on the performance of KSOP Class I Ambon office employees. This research is an empirical study, with the population being all employees of the class I Ambon port authority and Kesyahbandaran. The sampling technique uses an approach using the slovin formula and the sample size is 47 respondents. The analysis technique used is simple linear regression analysis, where the hypothesis test uses a t-test statistic to test the partial regression coefficients with a degree of significance used is 0.05 or 5%. The results of testing the responses of 47 respondents gave the conclusion of the study, namely, Discipline has a positive effect on the performance of class I Ambon port authority and Kesyahbandaran office employees. This is evidenced by the coefficient of determination obtained in this study of 0.825, meaning that the independent variable (Discipline) explains the dependent variable (employee performance) of 82.5% while the remaining 17.5% is influenced by other variables. Based on these results it can be concluded that Work Discipline Has a Positive Influence on the Performance of Class I Ambon Port Authority and Harbormaster Office Employees. Keywords: Work Discipline, Performance